«The slaughter genie»: Chilean soldiers and combat violence in the Pacific War (1879-1884) - González Puebla, Cristián (2024)
In several testimonies left by Chilean veterans of the Pacific War, it is possible to unveil situations in which the soldiers, alongside their companions, took the lives of their opponents in the heat of battle. In these memories, the extreme violence inflicted or experienced is obscured, since the actions of combat are generally attributed to a third person. However, these testimonies allow us to understand and approach the collective memory of Chilean fighters in the conflict of 1879-1884. They also allow us to see the soldiers as members of an emotional community that internalizes elements of combat psychology and physiology, which are vital in understanding the act of killing. All of this ends up highlighting terrible concrete experiences of the horrors of the battlefield, which represent a topic so far very little addressed in the historiography.